2007
DOI: 10.1111/j.1365-3024.2007.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the study of Trichinella spiralis TSL‐1 antigens in host immunity

Abstract: The observation on different hosts infected with Trichinella spiralis that recognized similar muscle larvae (ML) antigens and the fact that different monoclonal antibodies (mAb) had a similar reactivity to ML components prompted a proposal to define a useful classification system for these antigens. For this purpose, an international workshop provided a platform for the classification of T. spiralis antigens. ML antigens were classified in eight groups -- Trichinella spiralis larvae groups, TSL-1 to TSL-8. TSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 93 publications
0
21
1
Order By: Relevance
“…Rats maintain a resident population of mucosal mast cells in the lamina propria of the small intestine under homeostatic conditions (46). It has been suggested that mast cell activation might be a direct effect of the parasite, and such activation has been demonstrated in vitro following exposure of cultured mast cells to tyvelose-bearing T. spiralis Ags (47,48). In contrast, we found that parasite challenge in the absence of specific Abs did not cause significant RMCPII release.…”
Section: Discussioncontrasting
confidence: 54%
“…Rats maintain a resident population of mucosal mast cells in the lamina propria of the small intestine under homeostatic conditions (46). It has been suggested that mast cell activation might be a direct effect of the parasite, and such activation has been demonstrated in vitro following exposure of cultured mast cells to tyvelose-bearing T. spiralis Ags (47,48). In contrast, we found that parasite challenge in the absence of specific Abs did not cause significant RMCPII release.…”
Section: Discussioncontrasting
confidence: 54%
“…However, two issues, which were out of the scope of our current research, remain to be considered: the location of the detected ES L1 components, that is are they cargo, membrane or associated EVs proteins and the cellular origin of the detected EVs. Although helminth EVs may originate from the tegument, detection of ES L1 components within EVs suggests that their origin might be the stichosome, a multicellular organ that produces and releases ES L1 products …”
Section: Discussionmentioning
confidence: 99%
“…contain some functional proteins such as proteinases, proteinase inhibitors, heat shock proteins, glycosidases, kinases, phosphatases, endonucleases, MIFs, enolases, and DNA-binding proteins [21], determined mostly according to their structural and sequence similarity to proteins from another species with known function. Since T. spiralis ES L1 antigens are localized on the surface of the parasite [22] and in the nuclei of infected host cells [23], a possible role of these molecules may be in invasion of the enterocytes, establishment or maintenance of the nurse cell, and induction of immune response in host organism [24]. …”
Section: Es L1 Antigens Of T Spiralis Muscle Larvaementioning
confidence: 99%